2008
DOI: 10.1158/1535-7163.mct-07-2036
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of viral interleukin-6 expression of Kaposi's sarcoma–associated herpesvirus

Abstract: Kaposi's sarcoma -associated herpesvirus

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
22
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 53 publications
5
22
0
Order By: Relevance
“…Increases in intracellular viral DNA levels 4 days post-induction in BCBL1 TReX-RTA cells were very modest (∼5–7 fold), in agreement with other reports [48], [49]; this level was further decreased when cells were electroporated prior to induction. The low levels of intracellular viral DNA make it difficult to conclude definitively whether the knockdown of PAN RNA specifically inhibits viral DNA replication.…”
Section: Resultssupporting
confidence: 92%
“…Increases in intracellular viral DNA levels 4 days post-induction in BCBL1 TReX-RTA cells were very modest (∼5–7 fold), in agreement with other reports [48], [49]; this level was further decreased when cells were electroporated prior to induction. The low levels of intracellular viral DNA make it difficult to conclude definitively whether the knockdown of PAN RNA specifically inhibits viral DNA replication.…”
Section: Resultssupporting
confidence: 92%
“…Depletion of vIL-6 in these cells induces apoptosis and slows the rate of cell growth (Chen et al 2009a). Similar growth effects were observed with intracellularly delivered single-chain antibody and peptide-conjugated phosphorodiamidate morpholino oligomers (PPMO) directed to vIL-6 and its transcript (Kovaleva et al 2006; Zhang et al 2008). Fully ER-retained vIL-6 (cloned to include an ER-targeting KDEL motif) is capable of rescuing the growth effects mediated by vIL-6 depletion (Chen et al 2009a).…”
Section: Hhv-8 Latency Products and Autocrine Dysregulationsupporting
confidence: 53%
“…This was the primary goal of the present study. Previously, investigations touching on this issue have demonstrated that vIL-6 is capable of signaling in the ER when directed to this compartment by virtue of "KDEL" tagging (19), that ER-targeted single-chain antibodies specific for vIL-6 are able to inhibit vIL-6 signaling in HepG2 cells (16), and that vIL-6 depletion in PEL cells negatively affects cell growth (30). However, these results do not demonstrate that vIL-6 is naturally located predominantly in the ER, nor do they address the nature of the vIL-6-induced signaling complexes in this compartment or the biological activities specifically associated with ER signaling by vIL-6.…”
Section: Discussionmentioning
confidence: 99%